THE EFFECT OF HUMAN RESOURCE DEVELOPMENT, WORK EXPERIENCE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT CAMPINA ICE CREAM INDUSTRYTBK - Ananda Putri , Anika; Ubaidillah , Hasan; Andriani , Dewi (Universitas Islam Lamongan, 2025)
This study aims to analyze the influence of human resource development, work experience, and work motivation on employee performance at PT Campina Ice Cream Industry Tbk. Using quantitative methods with multiple linear regression analysis techniques, this study involved 145 respondents selected through random sampling techniques. The results of the study indicate that partially, human resource development has a positive and significant influence on employee performance with a regression coefficient of 0.305, where training programs are proven to increase employee productivity and adaptation. Work experience also has a significant effect with a regression coefficient of 0.232, indicating that longer experience supports work efficiency and understanding. Work motivation is the dominant variable with a regression coefficient of 0.425, which confirms the importance of financial incentives and non-financial rewards in improving employee performance. Simultaneously, these three variables explain 83.4% of the variation in employee performance, as indicated by the F value of 235.758. These findings confirm that human resource development, work experience, and work motivation are important elements in creating optimal performance, so companies need to focus on strategic management of these three factors to increase competitiveness.